TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PENGELOLAAN DANA TABUNGAN LEBARAN: Studi Kasus Di Desa Sumber Pandan Kecamatan Grujugan Kabupaten Bondowoso - Bachrul Ulum; Mohammad Shopyan (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
This research aims to determine the practice of managing savings funds for Eid packages in Sumber Pandan Village, Grujugan District, Bondowoso Regency. This research uses a qualitative approach. This type of research is in the form of field research. The location of this research is in Sumber Pandan Village, Grujugan District, Bondowoso Regency. Determination of informants using purposive. Data collection techniques use observation, semi-structured interviews and documentation. The data analysis uses descriptive data. Meanwhile, the validity of the data uses Validity, Reliability, Extended Observations, Triangulation, and Reference Materials. The results of the research show that the practice of managing savings funds for Eid packages in Sumber Pandan Village, Grujugan District, Bondowoso Regency, is that the management of savings funds is clearly carried out in matters related to good transactions and is managed by taking into account the profits that will be obtained later. Some savers believe that they don't know directly what their savings are used for. Most of them don't feel comfortable asking this because it is sensitive and private. Judging from sharia economic law, the implementation of Eid savings fund management according to Wahbah Zuhaili is halal for the manager (service provider) and according to Imam Abu Hanifah, he believes that the profit is shodaqoh. From this opinion, the researcher concluded that the Eid savings fund management transaction was permissible because the essence of Eid savings fund management was appropriate and fulfilled the elements of the wadiah yad dhamanah contract.